2017
DOI: 10.18632/oncotarget.20715
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 and STMN1 as prognostic markers in NSCLCs who received cisplatin-based adjuvant chemotherapy

Abstract: ObjectiveIn this study, we aimed to investigate the predictive effect of BRCA1, STMN1, MAPT and TUBB3 on the prognosis of patients with non-small cell lung cancer (NSCLC).MethodsSeventy NSCLC patients who received platinum-based chemotherapy from June 2009 to July 2011 were enrolled. The protein and mRNA levels of BRCA1, STMN1, MAPT and TUBB3 were determined. Survival time of the patients with NSCLC was also calculated.ResultsHigh expression of BRCA1 or low expression of STMN1 was associated with a better prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The results of the current meta-analysis which summarized 11 studies involving 1041 patients showed that positive BRCA1 expression was associated with a shorter OS and DFS without regional disparities. The conclusion was consistent with the results of the previous studies[ 18 , 21 , 25 , 26 ]. BRCA1 expression status could serve as a novel indicator for the assessment of prognosis and formulation of therapy strategy for resected NSCLC patients.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the current meta-analysis which summarized 11 studies involving 1041 patients showed that positive BRCA1 expression was associated with a shorter OS and DFS without regional disparities. The conclusion was consistent with the results of the previous studies[ 18 , 21 , 25 , 26 ]. BRCA1 expression status could serve as a novel indicator for the assessment of prognosis and formulation of therapy strategy for resected NSCLC patients.…”
Section: Discussionsupporting
confidence: 93%
“…Subgroup analysis on the detection method and tumor stage IIIb–IV showed no significant decrease in the heterogeneity. The OS of resectable 16,22,23,30 and inoperable 20,2426 NSCLC patients after platinum-based chemotherapy was clearly reported in four studies. For OS, there was no significant decrease in heterogeneity in subgroup analyses of both operable and inoperable NSCLC patients treated with platinum-based chemotherapy.…”
Section: Resultsmentioning
confidence: 97%
“…We thus showed that STMN1 levels were adversely associated with the clinical prognosis of AML patients. STMN1 has been found to be a potential prognostic marker for patients with different types of tumors, including colon cancer (Zhang et al, 2016), gastric cancer (Bai et al, 2017), pancreatic ductal adenocarcinoma (Li et al, 2015), meningioma (Wang et al, 2017a), gallbladder carcinoma (Bo et al, 2017), osteosarcoma (Zhao et al, 2018), esophageal squamous cell carcinoma (Ni et al, 2017), (Hsieh et al, 2010) and non-small cell lung cancer (Nie et al, 2015;Wang et al, 2017b). Our data and previous reports indicated that STMN1 may not be only a prognostic marker for solid cancer but could also serve as a prognostic marker for patients with leukemia.…”
Section: Discussionmentioning
confidence: 99%